Web accessible agroecological knowledge toolkit - CGIAR Research Program on Forests, Trees and Agroforestry (2021)
An initial implementation of the software is available online that will enable a community of users to access and further develop applications that facilitate combination of local and scientific knowledge to support agricultural innovation.